Update in Respiratory Diseases 2020
DOI: 10.5772/intechopen.90658
|View full text |Cite
|
Sign up to set email alerts
|

The Realm of Oncological Lung Surgery: From Past to Present and Future Perspectives

Abstract: In this chapter, a historical overview as well as an overview of state of the art of the surgical techniques for the treatment of lung cancer is outlined. The chapter focuses on the introduction of open surgery, video-assisted thoracic surgery (VATS), uniportal VATS (UVATS), and robotic-assisted thoracic surgery (RATS) techniques for lung resections. A short introduction on upcoming techniques and modalities is given. The currently available tools as three-dimensional (3D) computed tomography (CT), virtual rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…31,32 Based on some of these results it has been suggested that 3D modeling of CTs could contribute to better identification of anatomic abnormalities, recognition of suitable cases for pulmonary segment resections, and improved estimations of resection margins. 33 Consequently it is expected that with the recent advances in 3D CT and XR technology the very first 3D XR-guided planning and intraoperative guidance of an anatomic pulmonary resection could be performed in the near future. An essential aspect that would encourage the use of these modern technologies in the cardiothoracic surgical community is an open-minded, receptive attitude of surgeons toward these new digital interfaces.…”
Section: Virtual Guidance Of Pulmonary Resectionsmentioning
confidence: 99%
“…31,32 Based on some of these results it has been suggested that 3D modeling of CTs could contribute to better identification of anatomic abnormalities, recognition of suitable cases for pulmonary segment resections, and improved estimations of resection margins. 33 Consequently it is expected that with the recent advances in 3D CT and XR technology the very first 3D XR-guided planning and intraoperative guidance of an anatomic pulmonary resection could be performed in the near future. An essential aspect that would encourage the use of these modern technologies in the cardiothoracic surgical community is an open-minded, receptive attitude of surgeons toward these new digital interfaces.…”
Section: Virtual Guidance Of Pulmonary Resectionsmentioning
confidence: 99%
“…Other interesting examples of VR-based guidance and planning are navigational (ie, VR guided) bronchoscopy or augmented reality guided detection of small and deeply located lesions. 9 , 19 Further development and use of these novel technologies could potentially result in better preoperative diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Over the past few years, virtual reality (VR) devices and software are gaining popularity and have been shown to improve the understanding of patient anatomy by surgeons. 7 , 8 , 9 A VR platform has more features and functions than existing 2D or 3D planning software, including immersive and interactive manipulation, realistic in-depth perception, and visualization of complex relationships of anatomic structures that are ready at hand and can be applied by surgeons to gain a more realistic insight into a patient's anatomy. 8 , 10 Moreover, automated imaging algorithms could potentially create a more efficient planning by enabling automatic visualization of anatomic structures of interest.…”
mentioning
confidence: 99%